Properties of thermoplastic rice starch composites reinforced by cotton fiber or low-density polyethylene - Prachayawarakorn, J.; Sangnitidej, P.; Boonpasith, P. (My University, 2010)
Biodegradable polymer was prepared from thermoplastic rice starch (TPRS) plasticized by glycerol. In order to improve poor tensile properties and high water absorption of the TPRS, cotton fiber or low-density polyethylene (LDPE) were added into the TPRS matrix. The effect of maleic anhydride-grafted-polyethylene (MAPE) and vinyltrimethoxy silane (VTMS) compatibilizers on properties of the TPRS/LDPE specimens were also studied. The TPRS/cotton fiber, TPRS/LDPE, TPRS/LDPE/MAPE and TPRS/LDPE/VTMS samples were analyzed for tensile and morphological properties. The results showed that the incorporation of either cotton fiber or LDPE into the TPRS matrix caused the considerable improvement of tensile strength and Young's modulus. Moreover, water absorption of the TPRS samples was clearly reduced by the inclusion of cotton fiber or LDPE. In addition, phase morphology, thermal stability and biodegradability were carried out for different TPRS samples. Crown Copyright © 2010.
Keywords: Biodegradable polymer; Cotton fiber; Low-density polyethylene; Rice starch; Thermoplastic starch